Inhibition of mitogen‐activated protein kinase 1/2 in the acute phase of stroke improves long‐term neurological outcome and promotes recovery processes in rats. (17th December 2015) - Mostajeran, M.; Edvinsson, L.; Warfvinge, K.; Singh, R.; Ansar, S.
Abstract: Aim: Extracellular signal‐regulated kinase (ERK) 1/2 is activated during acute phase of stroke and contributes to stroke pathology. We have found that acute treatment with MEK1/2 inhibitors decreases infarct size and neurological deficits 2 days after experimental stroke. However, it is not known whether benefits of this inhibition persist long‐term. Therefore, the aim of this study was to assess neurological function, infarct size and recovery processes 14 days after stroke in male rats to determine long‐term outcome following acute treatment with the MEK1/2 inhibitor U0126. Methods: Transient middle cerebral artery occlusion was induced in male rats. U0126 or vehicle was given at 0 and 24 h of reperfusion. Neurological function was assessed by staircase, 6‐point and 28‐point neuroscore tests up to 14 days after induction of stroke. At day 14, infarct volumes were determined and recovery processes were evaluated by measuring protein expression of the tyrosine kinase receptor Tie‐2 and nestin. Levels of p‐ERK1/2 protein were determined. Results: Acute treatment with U0126 significantly improved long‐term functional recovery, reduced infarct size, and enhanced Tie‐2 and nestin protein expression at 14 days post‐stroke. There was no residual blockade of p‐ERK1/2 at this time point. Conclusion: It is demonstrated that benefits of early treatment with U0126 persist beyond subacute phase of ischaemic stroke in male rats. Prevention of ERK1/2 activation in the acute phase results in improved long‐term functional outcome and enhances later‐stage recovery processes. These results expand our understanding of the benefits and promise of using MEK1/2 inhibitors in stroke recovery.